THE HOUSEHOLD-TARGETED VIEW OF THE IMPLEMENTATION OF PNPM-MP ROUNDED FUNDS IN ATTEMPTING TO OVERCOME THE CASE POVERTY IN BALAI GADANG SUB-DISTRICT KOTO TANGAH DISTRICT PADANG CITY - Elparianti, Elparianti; Abbas, Ardi; Elvawati, Elvawati (Pendidikan Sosiologi, 2013)
The background of this research is the existence of basic assumption of difference between statistical data and reality in communities. This research is aimed at describing the household-targeted view on the implementation of PNPM-MP rounded funds in attempting to overcome the poverty.The approach applied is a qualitative approach with descriptive type. The determination of informants is made purposively. The technique of data sampling is through observations, interviews, and documentations. The analysis unit used is household-target and PNPM-MP implementations. The method of data analysis used is the deskriptive data analyzed as to the interactive model of analysis Miles & Hubermans.The results of research indicate that the household-target view of the PNPM-MP rounded fund implementation in trying to overcome the poverty generally can show that household-target provides a positive (good) sigh because of the felt assistance in borrowing rounded funds especially for the household-target whit smooth return and having previous entrepreneur. However, there is the view that the household-target assumes that the PNPM-MP implementation has not been useful directly, especially for the household-target accepting a fund in one-stage return.